Factors influencing hybrid rice adoption: a Bangladesh case - Mottaleb, Khondoker A.; Mohanty, Samarendu; Nelson, Andrew (Wiley, 2015)
As rice constitutes the major share in cereal consumption in South and East Asian countries that ranges from as low as 40 per cent in India to 97 per cent in Myanmar, to ensure food security, governments in these countries are encouraging farmers to adopt hybrid rice. This is mainly because hybrid rice provides a yield gain of 15–20 per cent over conventionally bred varieties in general. Yet, despite strenuous government efforts, farmers’ adoption rates have remained low in India, Bangladesh and Vietnam compared with China. Although studies often claim that higher seed costs and inferior grain quality are the major factors limiting hybrid rice adoption, very few studies examine the importance of socio‐economic factors and infrastructure in the adoption of hybrid rice. Using Bangladesh as a case, a comparative analysis has been made on the adoption of hybrid and modern varieties relative to traditional rice varieties and land allocation to these varieties. Econometric results indicate that general land characteristics, loan facilities and general infrastructure, such as roads, irrigation facilities and the availability of government‐approved seed dealers, significantly influence the adoption of hybrid and modern rice varieties and land allocation to these varieties compared with traditional varieties.